1988
DOI: 10.2118/16284-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbial Systems in Porous Media for EOR

Abstract: Summary. The use of microorganisms to enhance oil recovery has become a technically feasible technology for production from stripper wells (those that produce less than 10 B/D [1.6 m/d]). As a result of microbial growth and the production Of CO and/or chemicals, oil recovery can be effectively increased in certain reservoirs with temperatures and salinities hospitable to microorganisms. Research at the Natl. Inst. for Petroleum and Energy Research has led to development of laboratory faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 3 publications
1
24
0
2
Order By: Relevance
“…Near-wellbore plugging can inhibit the in-depth placement of the biological materials in the formation. A common method used to minimize near-wellbore plugging involves injecting microorganisms and nutrients sequentially into a formation with or without a brine s p a~e r .~~-~~>~~ 54*57,59, 60 The following is a summary of some other methods proposed in the literature for minimizing near-well plugging.…”
Section: In-depth Placementmentioning
confidence: 99%
“…Near-wellbore plugging can inhibit the in-depth placement of the biological materials in the formation. A common method used to minimize near-wellbore plugging involves injecting microorganisms and nutrients sequentially into a formation with or without a brine s p a~e r .~~-~~>~~ 54*57,59, 60 The following is a summary of some other methods proposed in the literature for minimizing near-well plugging.…”
Section: In-depth Placementmentioning
confidence: 99%
“…Previous studies have shown that the injection of nutrients in oil reservoirs will stimulate microbial metabolism (Bryant et al,1987, Jenneman et al, 1983Lin et al, 1996). The presence of gases, solvents, acids, and surface active agents have been detected in field stuides.…”
Section: Time (Hours)mentioning
confidence: 99%
“…Medium with Proteose Peptone (ME 2 ) This approach has been shown to be successful in a previous MEOR field trial (Bryant et al, 1987). Localized production of biosurfactant might be an efficient mechanism to recover residual oil.…”
Section: Time (Hours)mentioning
confidence: 99%
“…Non-viable or dead cells do not produce slime, precipitates, etc., so they act as particulate agents. Viable cells have the ability to adhere to rock and produce extra-cellular polysaccharides that cover cells and rock surfaces, forming a polymer film (Bryant and Douglas, 1987). These actions result in more effective plugging than particulate plugging by dead cells.…”
Section: Mechanisms Of Meormentioning
confidence: 99%